Geographies of postcolonialism spaces of power and representation - Sharp, Joanne P. (SAGE, 2023)
"Extensively revised, the second edition of Geographies of Postcolonialism introduces the principal themes and theories related to postcolonialism. Written from a geographical perspective, the text includes extended explanations of the cultural and material spaces of the colonial and postcolonial power and representation. Exploring postcolonialism through the geographies of imagination, knowledge and power the text analyses the history of western representations of the "Other" and the relationship between this and the European self-image but draws continuities to the present through examination of the persistent legacies of colonialism in the media, tourism, development policy and academia. The book engages with the important conceptual contributions of postcolonial theory and the limitations of this exposed by Indigenous scholars and those seeking to decolonise western-dominated institutions. Comprehensive and accessible, illustrated with learning features throughout, Geographies of Postcolonialism will be the key resource for students interested in the geographical and spatial dimensions of colonialism and postcolonialism"--